Absolute counts of botanical and zoological macro-remains obtained from the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
This dataset provides absolute counts of botanical and zoological macro-remains obtained from the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. Counts per taxon are presented against master sequence depth (m) and age (ka BP). The macroremains dataset consists of a total of 54 samples and provides information on terrestrial and aquatic ecosystem dynamics (Salonen et al., 2018). Macrofossil samples were prepared at 4–20 cm intervals from subsamples of mainly ca. 5 cm3. The sediment was sieved using a 100 μm mesh under running water and the residue examined using stereo and high-magnification light microscopes. The analyses were performed in the laboratories of the University of Helsinki, Finland.